Mindfulness-Based Treatment for Bipolar Disorder: A Systematic Review of the Literature - Sanja Bojic; Rodrigo Becerra (Europe's Journal of Psychology, 2017)
Despite the increasing number of studies examining the effects of mindfulness interventions on symptoms associated with Bipolar Disorder (BD), the effectiveness of this type of interventions remains unclear. The aim of the present systematic review was to (i) critically review all available evidence on Mindfulness Based Cognitive Therapy (MBCT) as a form of intervention for BD; (ii) discuss clinical implications of MBCT in treating patients with BD; and (iii) provide a direction for future research. The review presents findings from 13 studies (N = 429) that fulfilled the following selection criteria: (i) included BD patients; (ii) presented results separately for BD patients and control groups (where a control group was available); (iii) implemented MBCT intervention; (iv) were published in English; (v) were published in a peer reviewed journal; and (vi) reported results for adult participants. Although derived from a relatively small number of studies, results from the present review suggest that MBCT is a promising treatment in BD in conjunction with pharmacotherapy. MBCT in BD is associated with improvements in cognitive functioning and emotional regulation, reduction in symptoms of anxiety depression and mania symptoms (when participants had residual manic symptoms prior to MBCT). These, treatment gains were maintained at 12 month follow up when mindfulness was practiced for at least 3 days per week or booster sessions were included. Additionally, the present review outlined some limitations of the current literature on MBCT interventions in BD, including small study sample sizes, lack of active control groups and idiosyncratic modifications to the MBCT intervention across studies. Suggestions for future research included focusing on factors underlying treatment adherence and understanding possible adverse effects of MBCT, which could be of crucial clinical importance.